PENERAPAN ETIKA PROFESI DOKTER DALAM PELAYANAN KESEHATAN BAGI PASIEN - Mz, Putro Sucy Rezky; Sidi, Redyanto; Simarmata, Marice (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Professional ethics of doctors are an important foundation in the practice of quality health services. The application of professional ethics of doctors in health services for patients greatly determines the quality of services provided, both in terms of professionalism, safety, and patient comfort. This study aims to examine the application of medical professional ethics in providing health services to patients, focusing on aspects of honesty, medical confidentiality, and professional responsibility. The research method used was a literature study and interviews with medical personnel in several hospitals and clinics in Indonesia. The results show that although many doctors have implemented professional ethics well, there are still challenges in terms of effective communication between doctors and patients and adherence to the principle of medical confidentiality. In addition, the application of professional ethics is also influenced by cultural factors and the work environment in each health institution. Most doctors understand the importance of professional ethics, but their application is not yet fully optimal, especially in situations that require difficult decisions or conflicts of interest. This study provides recommendations to improve professional ethics training for doctors and create a work environment that supports the application of professional ethics in health services. It is hoped that with the implementation of better professional ethics, the quality of health services for patients can be further improved, create a more harmonious doctor-patient relationship, and reduce the risk of malpractice and patient complaints. Keywords: professional ethics, health services, medical confidentiality. Abstrak: Etika profesi dokter merupakan landasan penting dalam praktik pelayanan kesehatan yang berkualitas. Penerapan etika profesi dokter dalam pelayanan kesehatan bagi pasien sangat menentukan kualitas pelayanan yang diberikan, baik dari sisi profesionalisme, keamanan, maupun kenyamanan pasien. Penelitian ini bertujuan untuk mengkaji penerapan etika profesi dokter dalam memberikan pelayanan kesehatan kepada pasien, dengan fokus pada aspek-aspek kejujuran, kerahasiaan medis, dan tanggung jawab profesional. Metode penelitian yang digunakan adalah studi literatur dan wawancara dengan tenaga medis di beberapa rumah sakit dan klinik di Indonesia. Hasil penelitian menunjukkan bahwa meskipun banyak dokter yang sudah menerapkan etika profesi dengan baik, masih ada tantangan dalam hal komunikasi efektif antara dokter dan pasien serta kepatuhan terhadap prinsip kerahasiaan medis. Selain itu, penerapan etika profesi juga dipengaruhi oleh faktor budaya dan lingkungan kerja yang ada di setiap institusi kesehatan. Sebagian besar dokter memahami pentingnya etika profesi, tetapi penerapannya belum sepenuhnya optimal, khususnya dalam situasi-situasi yang memerlukan keputusan sulit atau konflik kepentingan. Penelitian ini memberikan rekomendasi untuk meningkatkan pelatihan etika profesi dokter serta menciptakan lingkungan kerja yang mendukung penerapan etika profesi dalam pelayanan kesehatan. Diharapkan dengan penerapan etika profesi yang lebih baik, kualitas pelayanan kesehatan bagi pasien dapat lebih ditingkatkan, menciptakan hubungan dokter-pasien yang lebih harmonis, dan mengurangi risiko malpraktik serta keluhan pasien. Kata kunci: etika profesi, pelayanan kesehatan, kerahasiaan medis.